THE ACTIVITY OF THROWING SPOKES AS PART OF THE DOWRY GIVING TRADITION IN THE SIPIROK COMMUNITY'S CUSTOMARY MARRIAGE SYSTEM - Hadiani Fitri (PT. Jurnal Center Indonesia Publisher, 2026)
Traditional marriage traditions are an important manifestation of maintaining the sustainability of local social and cultural values. One traditional practice still maintained by the Sipirok community is the mengumpar ruji activity as part of the dowry giving process. This activity is not only ceremonial, but also contains social, symbolic, and normative meanings that function as a mechanism for binding relationships between families. This study aims to analyze the meaning, function, and position of the mengumpar ruji activity in the Sipirok community's traditional marriage system. The research method used is qualitative with a descriptive-analytical approach, through literature review and normative analysis of traditional practices. The results show that mengumpar ruji is a symbol of sincerity, responsibility, and social recognition from the man towards the woman and her family. This tradition also functions as an instrument of social legitimacy in Sipirok traditional marriage. Thus, mengumpar ruji has a strategic role in maintaining social harmony and the sustainability of customary law amidst the social changes of modern society.